Assessing Alkali‐Metal Effects in the Structures and Reactivity of Mixed‐Ligand Alkyl/Alkoxide Alkali‐Metal Magnesiates. Issue 10 (27th January 2022) - Judge, Neil R.; Bole, Leonie J.; Hevia, Eva
Abstract: Advancing the understanding of using alkali‐metal alkoxides as additives to organomagnesium reagents in Mg−Br exchange reactions, a homologous series of mixed‐ligand alkyl/alkoxide alkali‐metal magnesiates [MMg(CH2 SiMe3 )2 (dmem)]2 [dmem=2‐[2‐(dimethylamino)ethyl]methylamino ethoxide; M=Li, 1 ; Na, 2 ; (THF)K, 3 ] has been prepared. Structural and spectroscopic studies have established the constitutions of these heteroleptic/heterometallic species, which are retained in arene solution. Evaluation of their reactivity towards 2‐bromoanisole has uncovered a marked alkali‐metal effect with potassium magnesiate 3 being the most efficient of the three ate reagents. Studies probing the constitution of the exchange product from this reaction suggest that the putative [KMgAr2 (dmem)]2 (Ar= o ‐OMe−C6 H4 ) intermediate undergoes redistribution into its single metal components [KAr]n and [MgAr(dmem)]2 (5 ). This process can be circumvented by using a different potassium alkoxide containing an aliphatic chain such as KOR' (R'=2‐ethylhexyl) which undergoes co‐complexation with Mg(CH2 SiMe3 ) to give [KMg(CH2 SiMe3 )2 (OR')]2 (7 ). This ate, in turn, reacts quantitatively with 2‐bromoanisole furnishing [KMgAr2 (OR')]2 (9 ) which is stable in solution as a bimetallic compound. Collectively this work highlights the complexity of these alkali‐metal mediated Mg−Br exchange reactions, where each reaction component can have a profound effect not only on the success of the reaction; but also the stability of the final metalated intermediates prior to their electrophilic interception. Abstract : Synthesis and isolation of several new mixed alkyl/alkoxide alkali‐metal magnesiates have allowed for assessing their stability in solution and their reactivity towards Mg−Br exchange using 2‐bromoanisole as a model substrate. Revealing a pronounced alkali‐metal effect, potassium magnesiates are more powerful exchange reagents although the constitution of the final products in these reactions is strongly dependent on the nature of the alkoxide employed.